Revolutionizing Nutrition Education: Trends, Innovations, and Prospects in Learning Media - Yulia, Cica (Universitas Islam Negeri Raden Intan Lampung, 2023)
This comprehensive study conducts an in-depth analysis to explore the dynamic landscape of nutrition learning media research, aiming to delineate evolving trends, developmental trajectories, and their consequential implications. Employing bibliometric analysis and content analysis approaches, this research uncovers distinct publication patterns and citation behaviors, spotlighting pronounced trends catalyzed by the COVID-19 pandemic, a testament to the adaptability of educational systems. The study identifies a spectrum of learning media formats, encompassing applications, websites, and game-based platforms, while emphasizing the prevalence of experimental and design methodologies within the research paradigm. Keyword clusters elucidate strategies integrating technology and catering to diverse target audiences. In conclusion, nutrition education media plays a pivotal role in addressing health and sustainability challenges. The study advocates for ensuring equitable access to digital resources and advocates for fostering interdisciplinary collaboration as pivotal facets for future research endeavors. Ultimately, this research significantly contributes to enhancing nutrition literacy and underscores the transformative potential of technology-driven education in empowering informed dietary decisions and augmenting overall health outcomes.